Utilisation of Cashew Nut Shell Liquid from Anacardium occidentale as Starting Material for Organic Synthesis: A Novel Route to Lasiodiplodin from Cardols - Santos,Maria Lucilia dos (1999)
As part of an ongoing program concerning utilisation of CNSL (Cashew Nut Shell Liquid) from Anacardium occidentale as starting material for the preparation of useful compounds, we describe the conversion of cardols (6-alkenylresorcinols) into lasiodiplodin, a naturally occurring 12-membered orsellinic acid type macrolide, which exhibits plant growth regulating and antileukemic properties.